EFEKTIVITAS FLAMOURIA GALAKSI SEBAGAI MEDIA ASTRONOMI DALAM MENINGKATKAN PEMAHAMAN DAN DAYA TARIK - Muhammad Hidayat; Abu Yazid Raisal; Arwin Juli Rakhmadi Arwin (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2025)
Astronomy is a science that is very close to children's daily lives, from recognizing time, day and night, to changes in the position of celestial bodies. However, learning astronomy at the primary and secondary education levels in Indonesia is still very limited, both in terms of materials and learning media available. This study aims to test the effectiveness of Flamouria Galaksi, a visual-interactive learning media in the form of glowing clouds, in improving students' understanding and interest in learning astronomy material, especially about galaxies and nebulae. The research method used is in accordance with development research and with a simple experimental approach with a quantitative approach through pre-test and post-test. The results showed an increase in student understanding by 91% after the use of Flamouria Galaksi media. This media is able to turn abstract astronomy concepts into a real and fun learning experience. The interactivity and aesthetic visuals proved to encourage students' active participation and increase their interest in astronomy. These findings suggest that the use of innovative media such as Flamouria Galaksi has great potential in supporting the STEAM learning approach and can be a solution to the low astronomy literacy among Indonesian students.